Dedifferentiated liposarcoma with abrupt transition of low-grade and high-grade dedifferentiation: A rare case report. (20th September 2021) - Wen, Yang; He, Xianglei; Zhao, Ming
Dedifferentiated liposarcoma is a unique subtype of liposarcoma, which has obvious histological heterogeneity. In affected patients, the condition typically manifests as the dedifferentiation of high-grade histological morphology, but it may also manifest as the dedifferentiation of low-grade histological morphology. In some cases, unique histological or immunophenotypic characteristics are observed. We describe, herein, a rare case of dedifferentiated liposarcoma, in which the high-grade and low-grade dedifferentiated components coexisted with a relatively sharp transition in pathology.